Design and Development of Radiated Heater with Temperature Control Program for Surface Plasmon Resonance Experiment. (January 2019) - Utomo, D K; Kurniawati, A; Hendro,; Viridi, S
Abstract: This research aims to design and to develop of radiated heater with temperature control program to be used in surface plasmon resonance experiments (SPR). The heater is made of NiCr solenoid with a value of 1 ohm resistance and 5 volt DC of voltage source. The control device in this experiment used the Arduino microcontroller which was connected to the LabVIEW software with an interface. The result that heating control program has been functioning in good condition with a deviation value at 3% from setpoint value at a distance of 0.8 cm, 1.0 cm and 1.2 cm from the heater surface.